A mind for what matters collected essays of F.F. Bruce - Bruce, Frederick Fyvie, 1910-1990 (Grand Rapids, MI Eerdmans, 1990)
Includes bibliographial references.
Keywords: Bible. N.T. -- criticism, interpretation, etc; Brethren movement -- theory and practice; Dead sea scrolls -- criticism, interpretation, etc